Deep learning with TensorFlow : take your machine learning knowledge to the next level with the power of TensorFlow 1.x /: take your machine learning knowledge to the next level with the power of TensorFlow 1.x. (2017) - Zaccone, Giancarlo; Karim, Md. Rezaul; Menshawy, Ahmed
No abstract available